2008
DOI: 10.3141/2046-04
|View full text |Cite
|
Sign up to set email alerts
|

Four Challenges to Incorporating Transportation Demand Management into the Land Development Process

Abstract: There are four primary challenges to incorporating transportation demand management (TDM) into the land development process, based on a review of growth management processes in Florida. These findings may be applicable to many cities outside Florida. The challenges include (a) the idea that TDM is valuable only if it can reduce travel, (b) transportation professionals considering TDM too late in the land development process, (c) the conflict between state and local governments for providing balance between mob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 6 publications
0
6
0
4
Order By: Relevance
“…A main consequence of the lack of an existing reference framework to support and foster the needed relationship between SUTP and the local urban development and planning instruments is that the results may show a lack of coordination that prevents the success of the plan, which, adopted hurriedly, suffers from improvisation. In fact, as Hendricks (2008) points out, 'It is recommended that transport demand management be represented in all phases of the land development process, including comprehensive planning and land development regulations.' Otherwise, the objectives of reducing the need to travel and the length of journeys, making it safer and easier for people to access jobs, shopping, services, etc., by transit and non-motorised modes, will not be addressed, and congestion and pollution will continue to increase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A main consequence of the lack of an existing reference framework to support and foster the needed relationship between SUTP and the local urban development and planning instruments is that the results may show a lack of coordination that prevents the success of the plan, which, adopted hurriedly, suffers from improvisation. In fact, as Hendricks (2008) points out, 'It is recommended that transport demand management be represented in all phases of the land development process, including comprehensive planning and land development regulations.' Otherwise, the objectives of reducing the need to travel and the length of journeys, making it safer and easier for people to access jobs, shopping, services, etc., by transit and non-motorised modes, will not be addressed, and congestion and pollution will continue to increase.…”
Section: Discussionmentioning
confidence: 99%
“…A common approach for coping with such a trend is to develop sustainable cities through urban mobility plans, a journey already started in many European cities where such processes have proved to be successful in reorientating decision-makers toward more sustainable travel choices without renouncing mobility, because transport demand management should not be associated with 'reducing travel' but instead with improved mobility (Hendricks, 2008). The paper, by a case studies-based methodology, presents some consolidated outcomes from such processes, trying to compare the different approaches chosen in four European countries, which can be considered state-of-theart examples in providing different sustainable mobility strategies for urban areas.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, increasing demands for multifamily housing and growing local government concerns about the infrastructure and service costs of low-density land use patterns have all generated increasing interest in collaborative regional planning efforts. Several studies have identified strategies for coordinating transportation and land use, including North Carolina (Rodriguez and Godschalk, 2003); Virginia (Miller et al, 2004); and Florida (Hendricks and Seggerman, 2005). However, this research focused primarily on topics such as travel demand tools, forecasting, and legislative options.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The role of TDM policy interactions may take place at the macro or micro level. Hendricks [18] reviewed "four primary challenges to incorporating TDM into the land development process: (a) the idea that TDM is valuable only if it can reduce travel; (b) transportation professionals considering TDM too late in the land development process; (c) the conflict between state and local governments for providing the balance between mobility and access; (d) the use of traffic analysis methods and standards that are geared toward preserving highway Level Of Service (LOS) for motor vehicles", and concluded that "TDM strategies are positioned poorly, internally to government leaders and partner departments and externally to land developers as a sort of mobility 'diet' imposed on the traveling public".…”
Section: New Dimensions In Active Forms Of Transportation and Demand mentioning
confidence: 99%